Engaging with Carol Bacchi : strategic interventions and exchanges - Bletsas, Angelique; Beasley, Chris (University of Adelaide Press, 2012)
"Carol Bacchi's scholarship is both substantial and wide-ranging. Beginning her academic career as a historian in the field of English-Canadian women's suffrage, Bacchi has made innovative and insightful contributions to the fields of feminist theory, critical policy studies, and post-structuralist theory. One of the characteristic traits of her scholarship is her interest in revising and revisiting analytic problems from a range of perspectives ... This book arose out of a conference organised by the Fay Gale Centre for Research on Gender at The University of Adelaide honouring Carol Bacchi's work and is intended to make that work accessible to a range of audiences."--Cover description